Leukocyte Profile of Tadpoles and Juveniles of Lithobates catesbeianus Shaw, 1802 (Anura) and the Effects of Nonylphenol and Cyproterone Acetate - De Gregorio, Lara S. [UNESP]; Franco-Belussi, Lilian [UNESP]; De Oliveira, Classius [UNESP] (Brazilian Herpetological Society, 2021)
Abstract. Amphibians are threatened with extinction worldwide, and one of the global causes is environmental pollution. Several toxicants can interfere with their immune system, making them more susceptible to disease, which also contributes to their decline. The contaminants 4-nonylphenol (NP), a detergent with estrogenic properties, and cyproterone acetate (CPA), an anti-androgenic medicine, are known to impair the immune system of some vertebrates, but the effects are understudied in anurans. In this study, we evaluated the effects of NP (at 1, 10, and 100 μg/L) and CPA (at 0.025, 0.25, and 2.5 ng/L) on leukocyte count in tadpoles and juveniles of Lithobates catesbeianus. We analyzed lymphocytes, neutrophils, basophils, eosinophils, monocytes, and thrombocytes in a proportional count and made comparisons between the groups. The experiments lasted 28 d, and the conditions were almost identical for both stages (varying only the volume of water). The tadpoles showed decreased lymphocytes and increased neutrophils at 1 μg/L NP and increased eosinophils at the two highest doses of CPA. The juveniles showed reduced neutrophils in all treatments with both compounds and increased thrombocytes (except at 2.5 ng/L CPA). Also, all dosages of CPA increased basophils. Although the life-stages had different response patterns, our study showed that NP and CPA altered the proportion of leukocytes on blood stream in both stages, probably as a response against the negative effects of the compounds, which might make the animals more susceptible to diseases and contribute to their decline.
Keywords: Ecotoxicology; Endocrine disrupting chemicals; Leukocytes; Pollutants